Role of FNAC in Breast Lump and its Histopathological Correlation - Shrestha, Richa; Vaidya, Pooja; Adhikari, Milan; Adhikari, Shiv Vansh; Shrestha, Anil (Journal of Nepalgunj Medical College, 2024)
Introduction: Breast malignancy is one of the common causes of morbidity and mortality among females. Screening of breast lumps by Fine Needle Aspiration Cytology (FNAC) is included in triple approach and is easy to perform. Accuracy of diagnosis can be further enhanced by histopathological confirmation. Aims: The role of FNAC in diagnosis of breast lumps and to determine its diagnostic accuracy. Methods: This was a hospital based prospective study conducted over the period of one year (from March 2023 to February 2024) in department of Pathology, Nepalgunj Medical College, Kohalpur, Nepal. Patients who presented with breast lump underwent FNAC with biopsy for histopathological study was included in the study. Cytological opinion was categorized according to International Academy of Cytology Yokohama System for Reporting Breast Fine Needle Aspiration Biopsy Cytopathology criteria reporting system. Histological correlation was carried out in patients who went surgical excision or biopsy of the lesion. Results: Most common diagnosis on cytology was fibroadenoma. According to International Academy of Cytology Yokohama reporting system C2 (benign) was most common reported category (19 cases). On histopathological study, 19 cases were benign and 13 cases were malignant with most common benign lesion being fibroadenoma and all malignant cases were Invasive ductal carcinoma. All cases diagnosed as malignant on cytology were concordant on histopathology. Three benign, one atypical and one suspicious on cytology were malignant on histopathological study. The sensitivity and specificity of FNAC was 84.2% and 69.2% respectively. Diagnostic accuracy of FNAC was 59.4%. Conclusion: Breast FNAC is a rapid and reliable tool for evaluation and have high sensitivity and specificity.